OBAMA AND NATASHA: HOW THE LAST LETTERS OF THEIR NAMES ARE PRONOUNCED - Sukrisno, Alim (Language Circle: Journal of Language and Literature, 2012)
This is a study about English pronunciation, particularly dealing with the pronunciation of the letter Ã¢â¬âa in final position of English words. The aim is to find a certainty of how to pronounce this letter, whether to be pronounced as [ÃÂ], [L] or any other sound. The data under observation are an exhausted list of words ending in -a letter collected from Oxford Advanced LearnerÃ¢â¬â¢s Dictionary (OALD). The result of the observation indicates that there are 847 words ending in Ã¢â¬âa. Those words consist of 683 general words, 75 names of persons, 74 names of countries, and 17 names ofÃÂ  states in the United States.ÃÂ  Out of the 847 words, 30 (0.03%) words have a deviating pronunciation pattern in their final Ã¢â¬âa letter. The majority of the words, 817 (96.45%) words demonstrate the sound [ÃÂ] in their finalÃÂ  Ã¢â¬âa letters. The final Ã¢â¬âa letter in most of the 30 words is pronounced as long [a:], and not as short [L] as often heard in the pronunciation of quite a few people. Since all of these 30 words are words of very low frequency of occurrence, they are not significant in contributing something of value to English pronunciation, so they can be neglected. Based on the result above, it can be concluded that all of the final Ã¢â¬âa letters in English words should be pronounced as [ÃÂ]; thus representing other English words, Obama is pronounced as [oÃÂ± ba:mÃÂ] and Natasha as [nÃÂta:Ã¢ËÂ«ÃÂ]. A suggestion coming out of the above finding is that we should, beyond doubt, pronounce the final letter Ã¢â¬âa in English words as [ÃÂ]. This suggestion will bear a teaching-learning consequence in the classroom.